2022
DOI: 10.1093/infdis/jiac129
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Transmission of Cytomegalovirus in a Rhesus Model Despite High-Level, Vaccine-Elicited Neutralizing Antibody and T-Cell Responses

Abstract: The development of a vaccine to prevent congenital human cytomegalovirus (HCMV) disease is a public health priority. We tested rhesus CMV (RhCMV) prototypes of HCMV vaccine candidates in a seronegative macaque oral challenge model. Immunogens included a recombinant pentameric complex (PC; gH/gL/pUL128/pUL130/pUL131A), a postfusion gB ectodomain, and a DNA plasmid that encodes pp65-2. Immunization with QS21-adjuvanted PC alone or with the other immunogens elicited neutralizing titers comparable to those elicite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…The homologous vaccine/challenge method was used because another study demonstrated that plasma from monkeys inoculated with either of two RhCMV strains exhibiting genetic drift in the coding regions for gB and some of those forming the PC (UCD52 and UCD56) do not cross‐neutralize the other non‐homologous strain 67 . The simplest interpretation of the absence of protective efficacy in the vaccine/oral challenge results in this study 66 is that despite high levels of antiviral immunity in the periphery circulating antiviral immunity is not operative at the oral mucosa, the site of RhCMV challenge. This putative scenario leads directly to two intertwined hypothetical scenarios.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…The homologous vaccine/challenge method was used because another study demonstrated that plasma from monkeys inoculated with either of two RhCMV strains exhibiting genetic drift in the coding regions for gB and some of those forming the PC (UCD52 and UCD56) do not cross‐neutralize the other non‐homologous strain 67 . The simplest interpretation of the absence of protective efficacy in the vaccine/oral challenge results in this study 66 is that despite high levels of antiviral immunity in the periphery circulating antiviral immunity is not operative at the oral mucosa, the site of RhCMV challenge. This putative scenario leads directly to two intertwined hypothetical scenarios.…”
Section: Discussionmentioning
confidence: 94%
“…There are multiple genetic/antigenic variants circulating in NHP at large breeding facilities. 66,67,70,71 Further, prior infection with endemic strains of RhCMV does not appear to restrict iatrogenic reinfections with RhCMV variants. [72][73][74][75][76][77] While RhCMV has been demonstrated to be fully capable of transplacental transmission following iatrogenic inoculation (intravenous), 42 there have been no reports of non-iatrogenic instances of congenital sequelae in neonatal or spontaneously aborted macaques.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations